Potential Health Effects of Grape Seed Extract on Female Albino Rats Fecundity (Article Review) - Alquraishi, Mohammed. K. S.; Ghani, Jenan Mahdi; Alqurashi, Nabaa K.; Al-Bayati, Maha M.; AlFatlawi, Mustafa H. (Medical Science Journal for Advance Research, 2025)
Background: There are many plant extracts and seeds with proven efficacy in the life sciences, some curative, some inhibitory, and some enhance, each with its own specific function and niche. In this study, we have compiled some sources from scientific websites concerned with life sciences and medical research across multiple scientific databases, including PubMed, Scopus, Web of Science, and Google Scholar We have clarified the impact of grape seed activity on the fertility of albino mice, along with related events and details. Aim of study: The study's focus is on demonstrating the effect of grape seed activity on the fertility of albino female mice. Introduction: Since the beginning of human civilization, medicinal plants have always remained a part and parcel of human, society to combat and treat different diseases. Materials and Methods: This review article was conducted based on a structured literature search and data synthesis Approach in accordance with established academic standards for narrative and semi Systematic reviews. Result: Our research indicated to the effect of alcoholic extract of grape seeds on the extent of improvement in the efficiency of the functioning of the ovaries and uteruses in female albino rats. Conclusion: We have concluded the effect of the alcoholic extract of grape seeds on the extent of improvement in the efficiency of the functioning of the ovaries and uterus in female albino rats. The results showed that there is a noticeable improvement in appearance and histology on the organs of the female reproductive system.